HSP70, a Novel Regulatory Molecule in B Cell-Mediated Suppression of Autoimmune Diseases. Issue 1 (8th January 2021) - Wang, Luman; Fu, Ying; Yu, Baichao; Jiang, Xuechao; Liu, Hongchun; Liu, Jun; Zha, Bingbing; Chu, Yiwei
Abstract: B cells have recently emerged as playing regulatory role in autoimmune diseases. We have previously demonstrated that human peripheral blood CD19 + CD24 hi CD27 + B cells have regulatory function both in healthy donors and in patients with autoimmune disease. However, the mechanism of this regulation is still not fully understood. In this study, microarrays were utilized to compare gene expression of CD19 + CD24 hi CD27 + B cells (regulatory B cells, Bregs) with CD19 + CD24 lo CD27 − B cells (non-Bregs) in human peripheral blood. We found that heat shock protein 70 (HSP70) expression was significantly upregulated in Bregs. In vitro studies explored that HSP70 inhibition impaired the regulatory function of peripheral blood Bregs. In mouse models of autoimmune disease, using HSP70-deficient mice or HSP70 inhibitors, Bregs suppressed effector cells and rescued disease-associated phenotypes that were dependent on HSP70. Mechanistically, Bregs secreted HSP70, directly suppressing effector cells, such as T effect cells. These findings reveal that HSP70 is a novel factor that modulates Breg function and suggest that enhancing Breg-mediated production of HSP70 could be a viable therapy for autoimmune disease. Graphical abstract: Unlabelled Image Highlights: HSP70 is highly expressed in human Breg, while it is almost not expressed in non-Breg. HSP70 is vital for Bregs to suppress immune responses in autoimmune diseases such as inflammatory bowel diseases and Hashimoto diseases. HSP70 modulated Breg suppressive function via directly secreting and targeting receptors on effected cells.